Enantioselective Povarov Reactions: An Update of a Powerful Catalytic Synthetic Methodology. Issue 2 (14th January 2022) - Lemos, Bárbara C.; Venturini Filho, Eclair; Fiorot, Rodolfo G.; Medici, Fabrizio; Greco, Sandro J.; Benaglia, Maurizio
Abstract: The enantioselective Povarov reaction is one of the most powerful synthetic strategy to synthesize chiral, highly functionalized 1, 2, 3, 4‐tetrahydroquinolines. The present Minireview aims to collect the most significant successful examples of highly efficient enantioselective catalytic protocols for this reaction, since 2014. A comprehensive discussion of different catalytic strategies employed in recent years to realize the enantioselective Povarov reaction is provided; the use of chiral phosphoric acids, thio(urea) and proline derivatives, as well as transition metal complexes will be presented. Additionally, this Minireview critically discusses the intriguing and yet obscure mechanistic pathways of this well‐known reaction, the controversial dispute between a concerted or a polar two‐step process. Abstract : One of the best‐studied routes to prepare chiral tetrahydroquinolines is known as the enantioselective Povarov reaction. In this Minireview enantioselective Povarov reactions published since 2014 are presented, according to the chiral catalyst used, either an organocatalyst or a metal complex, and discussed. When possible, special attention has been given to the rationalization of the stereochemical outcome of the reaction, discussing transition states and catalytic cycles.